Systematic review protocol for facilitators and barriers to integrating health services for traumatic brain injury and mental health or addictions - Angela Colantonio; Vincy Chan; Danielle Toccalino (BMJ Open)
Introduction In the most populous province of Canada, one in five adults and one in six students report a lifetime history of traumatic brain injury (TBI). These individuals were also more likely to report elevated psychological distress and use illicit substances compared with those without TBI. The need for integrated health services has been recognised globally, yet efforts to develop more comprehensive and effective care for TBI and mental health and/or addictions (MHA) continue to be challenged by the siloing of the two systems. This protocol is for a systematic review that describes the current types of integrated care for TBI and MHA and identifies the barriers and facilitators to integrating healthcare for these populations.Methods and analysis This review will systematically search MEDLINE, EMBASE, PsycINFO, CINAHL, Cochrane Central Register of Controlled Trials, Sociological Abstracts, and Dissertations & Theses Global. References of eligible articles will also be searched for additional relevant studies. The search strategy will include the use of text words and subject headings relevant to the concepts ‘TBI,’ ‘substance abuse, gambling, or mental health,’ ‘integrated healthcare,’ ‘barriers and facilitators,’ and ‘healthcare access.’ Two reviewers will independently screen all articles based on predetermined inclusion and exclusion criteria and perform quality assessment on eligible studies. A narrative synthesis will be conducted using the data abstracted by the two reviewers.Ethics and dissemination Findings from the systematic review will be published in peer-reviewed journals, presented at scientific meetings, and summarised for key stakeholders in the field of TBI and/or MHA. This protocol will form a systematic review that holds the potential to impact policy and planning in the development of integrated person-centred care for TBI and MHA and addresses a recognised gap in TBI care.Trial registration number CRD42018108343